Investigating the properties of stripped-envelope supernovae; what are the implications for their progenitors?. Issue 2 (7th December 2018) - Prentice, S J; Ashall, C; James, P A; Short, L; Mazzali, P A; Bersier, D; Crowther, P A; Barbarino, C; Chen, T-W; Copperwheat, C M; Darnley, M J; Denneau, L; et al.
ABSTRACT: We present observations and analysis of 18 stripped-envelope supernovae observed during 2013–2018. This sample consists of five H/He-rich SNe, six H-poor/He-rich SNe, three narrow lined SNe Ic, and four broad lined SNe Ic. The peak luminosity and characteristic time-scales of the bolometric light curves are calculated, and the light curves modelled to derive 56 Ni and ejecta masses ( M Ni and M ej ). Additionally, the temperature evolution and spectral line velocity curves of each SN are examined. Analysis of the [O i ] line in the nebular phase of eight SNe suggests their progenitors had initial masses <20 M⊙ . The bolometric light curve properties are examined in combination with those of other SE events from the literature. The resulting data set gives the M ej distribution for 80 SE–SNe, the largest such sample in the literature to date, and shows that SNe Ib have the lowest median M ej, followed by narrow-lined SNe Ic, H/He-rich SNe, broad-lined SNe Ic, and finally gamma-ray burst SNe. SNe Ic-6/7 show the largest spread of M ej ranging from ∼1.2–11 M⊙, considerably greater than any other subtype. For all SE–SNe < M ej > = 2.8 ± 1.5 M⊙ which further strengthens the evidence that SE–SNe arise from low-mass progenitors which are typically <5 M⊙ at the time of explosion, again suggesting M ZAMS <25 M⊙ . The low < M ej > and lack of clear bimodality in the distribution implies <30 M⊙ progenitors and that envelope stripping via binary interaction is the dominant evolutionary pathway of these SNe.